Blockade of Crk eliminates Yki/YAP-activated tumors via JNK-mediated apoptosis in Drosophila. - Kakemura, B.; Igaki, T. (Communications biology, 2024)
Selective elimination of cancer cells without causing deleterious effects on normal cells is an ideal anti-cancer strategy. Here, using Drosophila cancer model, we performed an in vivo RNAi screen for anti-cancer targets that selectively eliminate tumors without affecting normal tissue growth. In Drosophila imaginal epithelium, clones of cells expressing oncogenic Ras with simultaneous mutations in the cell polarity gene scribble (Ras[V12]/scrib[-/-]) develop into malignant tumors. We found that knockdown of Crk, the Drosophila ortholog of human CRK (CT10 regulatory kinase) and CRKL (Crk-like) adapter proteins, significantly suppresses growth of Ras[V12]/scrib[-/-] tumors by inducing c-Jun N-terminal kinase (JNK)-mediated apoptosis, while it does not affect growth of normal epithelium. Mechanistically, Crk inhibition blocks Yorkie (Yki)/YAP activity by impairing F-actin accumulation, an upstream event of Yki/YAP activation in tumors. Inhibition of Yki/YAP in tumors causes intracellular JNK signaling to be used for apoptosis induction. Given that molecules and signaling pathways identified in Drosophila are highly conserved and activated in human cancers, our findings would provide a novel, to the best of our knowledge, anti-cancer strategy against YAP-activated cancers.